Integrating Gamification Strategy to Stimulate Students' Interest and Motivation on English Lesson at SMP Negeri 26 Makassar - Awalia Azis; Putri, Anindia; Nur Qalbi (FKIP Unismuh Makassar, 2022)
The goal of this research is to clearly identify more about the problem of the gamification learning approach by using teaching materials based on gamification achievement in face-to-face learning and how Android applications used as a way of mobile learning to overcome these problems. This study aims to examine the application of gamification to stimulate students' interest and motivation in the concept of mobile learning by using a learning resource named Lima Sahabat for learning among seventh graders of junior high school. A Quasi-experimental study design was used (non-equivalent control group Pre-Test and Post-Test designs). The population in this study were all the seventh grade students (224 students) and the samples were class VII.2 (31 students) and VII.3 (31 students). The result for interest there was an increase of 1,9 points for the control class (72,74 – 70,84), while in the experimental class there was an increase of 14,52 points (78,23 – 63,71) and the result of motivation there was an increase of 1,03 points for the control class, while in the experimental class there was an increase of 18,87 points. The significance value of 0.000 for the learning interest variable and 0.001 for the learning motivation variable is less than 0.05 (5%), the null hypothesis (Ho) was rejected and the alternative hypothesis (H1) was accepted. By accepting the alternative hypothesis (H1), it can be concluded that gamification effects the interest and learning motivation of class VII students at SMP Negeri 26 Makassar in English Lesson.